(untitled) (Research, Society and Development, 2022)
Introduction: The Academic Leagues are student groups that aim to improve the study and skills acquired during graduation in a specific area of knowledge under the supervision of an advisor. This study aims to report the experience during the creation and legal regularization of an Academic League of Medicine in the field of Bioethics. Methodology: It is a qualitative, descriptive type of research that will report retrospectively the motivation, the technical, administrative, and legal procedures involved in the creation and regularization of a league. Results: In the current study, participation in an AL is something that grows gradually, proof of which are the impacts caused on the undergraduate student. Participating in this project is a benefit of high power in the curriculum and an excellent opportunity to improve the knowledge about the subject in focus. Furthermore, this study describes how the contribution of participation and organization in an academic league is a factor of mutual appreciation due to the exchange of knowledge and experiences, which are positive points in personal and professional formation. Conclusion: The present study evidence and concludes that the path of the whole process is arduous and that the presence of very scarce literature shows how fundamental it is to cultivate the development of studies that aim at this description of experience since experience coming from LABERN, the founding directors have become proactive, persistent, and admiring members of the axes of Bioethics.